Analisis Desain Kemasan Makanan Ringan Karya Siswa Kelas IX SLBE Negeri Pembina Tingkat Provinsi Ditinjau Dari Elemen Visual Seni Rupa - Annisa Amalia; Daulat Saragi; Raden Burhan Surya Nata Diningrat (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Based on the background that has been explained by the research, 50% of students who have not yet been able to understand graphic design learning materials are because students who have acquired these skills do not have such educational backgrounds. This research aims to determine and describe the abilities of SLBE students in applying visual elements of fine arts to snack packaging designs created by class IX SLBE Negeri Pembina Province Level students. This research includes quantitative and qualitative descriptive research. The results of this research explain that students' understanding of packaging design using the CorelDraw application has increased quite significantly compared to before. This can be seen from the results of the students' work on pre-test and post-test packaging designs which were produced quite well. From the results of the assessment of work I which obtained an average score (r) = 79 and the results of the assessment of work II which obtained an average score (r) = 81, it can be concluded that the results of the post-test work that had been designed by the students received an average score of average (r) = 80 (good) and experienced an increase of 8%.